Comportamiento agronómico de las hortalizas col verde (Brassica oleracea var. viridis), col morada (Brassica oleracea var. capitata), con dos tipos de fertilizantes orgánicos en el centro experimental “La Playita - Palacios Riera, Javier Urcesino (2014)
In the Experimental Center "La Playita", of the Cotopaxi Technical University, La Maná Canton, a research was carried out in order to know the agronomic performance of green and red cabbage with organic fertilizers that were vermicompost, water hyacinth, 50% vermicompost + 50% water hyacinth and a witness, with five replicates; the design was the Randomized Complete Block Design (RCBD), the best treatment for green cabbage and red cabbage was with water hyacinth. In green cabbage with this fertilizer was obtained the following results: plant height (22.06 cm), number of leaves (11.16), long leaves (21.06 cm), leaf width (17.43 cm), cabbage circumference (55.53 cm), and cabbage weight (388.86 g)....